If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(1 + -6b) = -200 (1 * -8 + -6b * -8) = -200 (-8 + 48b) = -200 Solving -8 + 48b = -200 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 48b = -200 + 8 Combine like terms: -8 + 8 = 0 0 + 48b = -200 + 8 48b = -200 + 8 Combine like terms: -200 + 8 = -192 48b = -192 Divide each side by '48'. b = -4 Simplifying b = -4
| 3=-6(y-4)-3y | | 4(4n+6)=120 | | 8(6+4x)=112 | | 6.72+8= | | 102=-6(4x+3) | | 82=2(1+5n) | | 4n-10=4+20 | | 130=5(1+5x) | | Y=120+-9.5x | | 2cos(2x)=-1 | | -126=-6(1+5n) | | 10(x-3)=70 | | 1+2(-8-8n)=-143 | | 5=4a+-7 | | -95=-8(3n-6)+1 | | 4x-2-7= | | 3a+b+5a+2b= | | 5x+10=305 | | -1-3(1+3r)=-31 | | X^2-3x+37=9x+5 | | 4X+3=2X+103 | | 81-3=n | | -5k+8(-2k-8)=-169 | | (-8x-5)(x+6)=(x+3)(-8x-8) | | 5a+4b+2a= | | -33=3(-3k-2) | | 10y+18=3(5-7)+5y | | Log[3](4x+3)=0 | | 5a+3b+2a= | | y+29=4y+48 | | 2a+5b+3a= | | -2m-4m+10= |